Listening Comprehension Challenges: Analyzing EFL Students in the English Teacher Education Program at Universitas Mulawarman - Saputri, Alya; Ahada, Ichi; Setiawan, Iwan; Sucahyo, Didik (Borneo Educational Journal (Borju), 2025)
EFL students still struggle at several points in the listening process, despite the fact listening comprehension is an essential part of improving their listening abilities. The purpose of this study is to determine the listening comprehension challenges EFL students enrolled in Mulawarman University's English teacher education program face. Data were gathered using a descriptive study methodology also a listening comprehension-focused questionnaire. As per the results, pupils struggle greatly in all three stages of listening—perception, parsing, also utilization—with the perception phase exhibiting the most severe problems. These difficulties have a major effect on how well they listen overall. The study's findings are meant to give lecturers important information for creating engaging classes also training methods for listening skills.